The cognitive effects and decrements following concussion - Tracey Covassin; Robert J Elbin (Dove Medical Press, 2010)
Tracey Covassin, Robert J ElbinMichigan State University, Department of Kinesiology, East Lansing, MI, USAAbstract: Sports-related concussion is an injury that continues to receive attention from both the popular media and sports medicine community. The many different symptom presentations and cognitive decrements that follow concussions, have made this injury difficult to detect and manage. Furthermore, concussed athletes should not always be entrusted to appropriately self-report their concussion symptoms; therefore the burden falls on the clinician and coach. Recent management recommendations call for using a multi-faceted approach to managing concussion, which consists of neurocognitive testing before (ie, baseline/preseason) and after injury. In addition age, sex, and previous history of concussion have been found to influence the risk and recovery from this injury.Keywords: cognitive function, neurocognitive testing, concussion